Improvement of gas sensing selectivity of vanadium pentoxide nano-structures towards sulphur dioxide by gold doping - Mokwena, Mick Molukie (My University, 2023)
A facile reflux method was used to synthesise undoped and Au-doped V2O5 nanoparticles powder samples at concentrations ranging from 1 wt% to 5 wt%. The prepared samples’ structural and optical properties were examined using x-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDS),Brunuaer-Emmett-Teller (BET),ultraviolet-visible spectroscopy (UV-Vis) and Fourier transform infrared spectroscopy (FT-IR). The XRD diffractograms confirmed that the prepared samples have an orthorhombic crystal structure. The lattice parameters of undoped and Au-doped V2O5 samples were determined and found to match with those of bulk V2O5. The average crystallite size of the undoped and Au-doped V2O5 was found to increase at low Au concentrations (1 wt% - 3 wt%) and decrease at high Au concentrations (4 wt% - 5 wt%) due to an increased number of nucleation sites. The SEM images showed morphological changes from spherical to nanorods for undoped and doped V2O5 respectively. The elemental composition of the undoped and Au-doped V2O5 nanoparticles were confirmed using EDS. The same was done for the 2 wt% Au-doped V2O5 sample that was contaminated by mercury (Hg). BET was used to probe the surface area of the undoped and Au-doped V2O5 while also confirming that all the samples were mesoporous. The band gap of the undoped and Au-doped V2O5 samples were determined from the UV-Vis absorption spectra and found to increase at high Au concentrations. The functional groups present in all prepared samples were investigated using FTIR spectroscopy.
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2023
Keywords: Gas sensing; Vanadium Pentoxide; Sulphur dioxide; Gold doping; Nanostructured materials; Sulphur dioxide; Vanadium oxide; Vanadium pentoxide